Lorca and León Felipe: From "Drop a Star" to "Poeta en Nueva York" - Hernández Fernández, Teresa (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Two very different spanish poets, León Felipe and García Lorca, compose two contemporary lyrical works inspired in the city of New York: León Felipe wrote Drop a Star in 1930 and Lorca elaborated the first draft of Poeta en Nueva York during the year (June 26, 1929 - March 30, 1930) that he stayed at Columbia’s University. The huge modern city and its contrasts produces a reaction in both poets in recurrent cycles of love/hate, fastinationldesperation. This paper contains the main structural analogies and differences between Drop a Star and Poeta and establishes explicit connections with the Anglo-American lyric (W. Whitman) and the implicit influence of the romantic ideal (J. Keats).